A randomised single blind control study to assess the effect of intrapartum amnioinfusion on maternal caesarean section rate and fetal outcome in a tertiary care centre - Fonseca, Michelle; Dwivedi, Jyotsna S. (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2017)
Background: The procedure of instilling normal saline/Ringer’s lactate into the uterine cavity is called amnioinfusion. Objective of present study was to assess the effect of intrapartum amnioinfusion on maternal caesarean section rate and fetal outcome in a tertiary care centre in cases of meconium stained amniotic fluid. Methods: A total of 160 women at term in labor with meconium stained amniotic fluid were randomized into two groups: study and control group. The study group received transcervical amnioinfusion at detection of MSAF. The control group was given the routine obstetric care. Both groups were started on O2 and intrapartum monitoring. The outcomes in both groups were analyzed statistically. Results: The control group had caesarean section rate of 45% and in the study group it was 31.25%. The difference was statistically significant. The outcome in the neonate was assessed on the parameters such as respiratory distress, neonatal intensive care unit admission, meconium aspiration syndrome, neonatal deaths. Conclusions: Amnioinfusion in cases of meconium stained amniotic fluid cases significantly reduces the risk of meconium aspiration syndrome. It also decreases the need for operative intervention thus reducing the risk of maternal morbidity and mortality.